Chill-tolerant Gryllus crickets maintain ion balance at low temperatures. (June 2015) - Coello Alvarado, Litza E.; MacMillan, Heath A.; Sinclair, Brent J.
Graphical abstract: Highlights: Chill-susceptible insects lose ion and water balance in the cold. Cold acclimation and evolution can improve cold tolerance. Cold-tolerant crickets can better maintain ion and water balance in the cold. Abstract: Insect cold tolerance is both phenotypically-plastic and evolutionarily labile, but the mechanisms underlying this variation are uncertain. Chill-susceptible insects lose ion and water homeostasis in the cold, which contributes to the development of injuries and eventually death. We thus hypothesized that more cold-tolerant insects will better maintain ion and water balance at low temperatures. We used rapid cold-hardening (RCH) and cold acclimation to improve cold tolerance of male Gryllus pennsylvanicus, and also compared this species to its cold-tolerant relative ( Gryllus veletis ). Cold acclimation and RCH decreased the critical thermal minimum (CTmin ) and chill coma recovery time (CCR) in G. pennsylvanicus, but while cold acclimation improved survival of 0 °C, RCH did not; G. veletis was consistently more cold-tolerant (and had lower CCR and CTmin ) than G. pennsylvanicus . During cold exposure, hemolymph water and Na + migrated to the gut of warm-acclimated G. pennsylvanicus, which increased hemolymph [K + ] and decreased muscle K + equilibrium potentials. By contrast, cold-acclimated G. pennsylvanicus suffered a smaller loss of ion and water homeostasis during cold exposure, and this redistribution did not occur at all in cold-exposed G. veletis . The loss of ion and water balance was similar between RCH and warm-acclimated G. pennsylvanicus, suggesting that different mechanisms underlie decreased CCR and CTmin compared to increased survival at 0 °C. We conclude that increased tolerance of chilling is associated with improved maintenance of ion and water homeostasis in the cold, and that this is consistent for both phenotypic plasticity and evolved cold tolerance.